A comparison between childhood and adult onset systemic lupus erythematosus adjusted for ethnicity from the 1000 Canadian Faces of Lupus Cohort. (25th February 2019) - Kim, Hyein; Levy, Deborah M; Silverman, Earl D; Hitchon, Carol; Bernatsky, Sasha; Pineau, Christian; Smith, C Doug; Tucker, Lori; Petty, Ross; Arbillaga, Hector; Zummer, Michel; Hudson, Marie; et al.
Abstract: Objective: Childhood-onset SLE (cSLE) manifests differently than adult-onset SLE (aSLE). This study determined whether ethnic differences contribute to the differences in clinical presentation between the two groups. Methods: This cross-sectional study used data from a multi-centred registry from eight adult and four paediatric Canadian centres gathered at study entry. We compared the frequency of clinical manifestations and autoantibodies between aSLE and cSLE. For those with a significant difference, a multivariable logistic regression was performed, adjusting for ethnicity, SLE onset (cSLE vs aSLE), disease duration and centre. Disease activity and damage between aSLE and cSLE were compared after stratifying by disease duration. Results: Of 552 aSLE subjects, 502 (90.9%) were female and 381 (69.0%) were Caucasian. Mean age at diagnosis was 37.0 ± 13.6 years and disease duration 10.9 ± 9.6 years. Of 276 cSLE subjects, 231 (83.7%) were female and 101 (36.6%) were Caucasian. Mean age at diagnosis was 12.7 ± 3.3 years and disease duration 5.6 ± 8.2 years. In multivariable regression analysis, aSLE was associated with decreased odds of having a neurologic disorder (odds ratio = 0.49) and increased odds of having aCL antibodies (odds ratio = 1.85). Disease activity and damage accrual scores were higher in aSLE than cSLE within the same disease duration strata, although the differences were not clinically significant. Ethnicity was not associated with any differences in clinical manifestations or autoantibody frequency between aSLE and cSLE. Conclusion: Although a crude comparison of aSLE and cSLE yielded several differences in clinical symptoms and autoantibodies, this difference was not attributable to ethnic differences between aSLE and cSLE.